1998
DOI: 10.1080/02844319850158921
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism in Myocutaneous Flaps Studied by in Situ Microdialysis

Abstract: The aim of this investigation was to follow the metabolism of myocutaneous flaps using microdialysis. After subcutaneous implantation of a microdialysis catheter into the flap tissue, serial samples were collected and changes in composition of the extracellular fluid assessed. Ten women underwent reconstructions with transverse rectus abdominis myocutaneous (TRAM) or latissimus dorsi flaps. Glucose, glycerol, and lactate concentrations were measured in the flaps and compared with those in adipose control tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…The procedure has reached widespread application in neurosurgery 12,13 and the neurointensive care unit, 14-16 cardiovascular 17 and plastic surgery. 18,19 Furthermore, it allows monitoring metabolism in skeletal muscle, 20,21 adipose tissue, [22][23][24] and tissue glucose in diabetes mellitus diseases. 25 It also has been used to monitor liver grafts in rats.…”
mentioning
confidence: 99%
“…The procedure has reached widespread application in neurosurgery 12,13 and the neurointensive care unit, 14-16 cardiovascular 17 and plastic surgery. 18,19 Furthermore, it allows monitoring metabolism in skeletal muscle, 20,21 adipose tissue, [22][23][24] and tissue glucose in diabetes mellitus diseases. 25 It also has been used to monitor liver grafts in rats.…”
mentioning
confidence: 99%
“…Microdialysis has been utilized previously for muscle metabolic studies at rest, where 20 min of total ischaemia by the use of a tourniquet approximately doubled the microdialysate lactate concentration [10], also during static exercise where microdialysate lactate concentrations increased with increasing contraction force [11] and under perioperative ischaemic conditions in skin flaps [12]. The technique has also recently been used in dynamically exercising muscle where it was shown that microdialysate lactate and glucose recovery, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques have been used to demonstrate oxygen delivery [9], oxygen homeostasis or blood flow by dye diffusion [10], laser Doppler flowmetry [11], oxygen measurements [12,13] or microdialysis [14,15,16]. However, all these techniques have their limitations in assessing blood perfusion only indirectly.…”
Section: Introductionmentioning
confidence: 99%